Possibilities of decoupling for China’s energy consumption from economic growth: A temporal-spatial analysis - Boqiang Lin; Wang, Miao (Energy (Oxford), 2019)
It is highly important to clarify the determinants of China’s energy consumption for the smooth implementation of energy conservation. For this purpose, this paper discusses the contribution of China’s different economic sectors to decoupling progress. Then, it uses an extended logarithmic mean Divisia index (LMDI) method to decompose China’s energy consumption into seven factors. The major findings indicate that during the 2000–2016 period, (1) the decoupling status between China’s economy and energy consumption were determined largely by the secondary industry; (2) the positive contribution of three sectors to the decoupling process was ranked as follows: primary industry>tertiary industry>secondary industry; (3) China’s energy consumption showed a growing trend, and the expansion of per capita fixed asset investment was the main factor responsible for the energy consumption increase, especially in some provinces whose investment structure was skewed towards energy-intensive industries. Additionally, population growth had mild positive impacts on the energy consumption increase; (4) declines in energy intensity and investment efficiency were two major contributors to energy-saving. However, economic structure, energy structure, and spatial structure adjustment failed to reduce energy consumption but had overall positive impacts on the energy consumption increase. Finally, several policy recommendations related to reducing energy consumption are proposed. •The empirical analysis was conducted at both national and provincial levels.•Decoupling status was determined largely by the secondary industry.•Per capita fixed asset investment was dominant for energy consumption increase.•The decline in energy intensity and investment efficiency contributed to energy-saving.